Rate and severity of radiological features of physical abuse in children during the first UK-wide COVID-19 enforced national lockdown. Issue 6 (17th February 2022) - Stivaros, Stavros; Paddock, Michael; Rajai, Azita; Cliffe, Helen; Connolly, Daniel JA; Dineen, Robert A; Dixon, Rachel; Edwards, Harriet; Evans, Emily; Halliday, Katherine; Jackson, Kandise; Landes, Caren; et al.
Abstract : Rate and severity of radiological features of physical abuse in children during the first UK-wide COVID-19 enforced national lockdown. Objective: To assess the number, type and outcome of radiological investigations for children presenting to hospital with suspected physical abuse (SPA; including abusive head trauma) during the first national COVID-19 enforced lockdown compared with the prelockdown period. Design: Multicentre, retrospective, observational, interrupted time series analysis. Setting: Eight secondary/tertiary paediatric centres between January 2018 and July 2020 inclusive. Participants: 1587 hospital assessed children undergoing radiographic skeletal surveys (SkS) and head CT imaging performed for SPA/child protection concerns. Main outcome measures: Incidence and severity of fractures identified on SkS; head injury (composed of incidence rates and ratios of skull fracture, intracranial haemorrhage (ICH) and hypoxic ischaemic injury (HII)) on head CT imaging; and ratio of antemortem and postmortem SkS. Results: 1587 SkS were performed: 1282 (81%) antemortem, 762 (48%) male, and positive findings in 582 (37%). Median patient age was 6 months. There were 1.7 fractures/child prelockdown versus 1.1 fractures/child during lockdown. There was no difference between positive/negative SkS rates, the absolute ratio of antemortem/postmortem SkS or absolute numbers of head injury occurring between January 2018 and February 2020 and the lockdown period April–July 2020. Likewise, prelockdown incidence and rates of skull fracture 30/244 (12%), ICH 28/220 (13%) and HIE 10/205 (5%) were similar to lockdown, 142/1304 (11%), 171/1152 (15%) and 68/1089 (6%), respectively. Conclusion: The first UK COVID-19 lockdown did not lead to an increase in either the number of antemortem or postmortem radiological investigations performed for SPA, or the number or severity of fractures and intracranial injuries identified by these investigations. Abstract : There has been conflicting evidence on whether incidents of physical child abuse became more frequent during the 2020-21 Covid-related lockdowns. This study of abuse-related radiological investigations from hospitals in northern England revealed no such increase.